Professional Development on Data-Based Individualization: A Mixed Research Study. (May 2023) - Bruhn, Allison L.; Estrapala, Sara; Mahatmya, Duhita; Rila, Ashley; Vogelgesang, Kari
Data-based individualization (DBI) is a process of collecting and analyzing data on students' response to intervention and then making intervention adaptations accordingly. Although this process can lead to better student outcomes, very few teachers are trained in the components of DBI, particularly in relation to behavior. Improving practice requires not only ongoing professional development but also understanding about how teachers' experiences in training can lead to better outcomes. Within the context of implementing a behavior intervention, the purpose of this study was to evaluate how participating in ongoing professional development on DBI affects teachers' perceptions of themselves in relation to the DBI framework over time. Using a convergent, parallel mixed-methods research design, we evaluated the conceptual understanding, self-efficacy, and perceptions associated with DBI before, during, and after professional development of 16 general and special education teachers. Data analysis indicated teachers reported significant improvements in all three areas over time. Qualitative data indicated active practice and collaboration with other professionals contributed to these improvements. Key findings, limitations, and future directions are discussed.